Effects of distributed leadership on teachers’ job satisfaction: The mediating role of teacher collaboration - Li Ma; Ying Gu (PLoS ONE, 2026)
Teachers are the primary resource for educational development and the fundamental force behind building and achieving a high-quality education system. Researching strategies to improve teacher job satisfaction is crucial for the high-quality development of teachers. Being empirical in nature and based on distributed leadership theory, this study uses data from OECD’s TALIS 2018 teachers survey. The multiple regression analysis model is used to analyze the impact of distributed leadership on teachers’ job satisfaction in an international context, with a particular focus on the mediating effect of teacher collaboration. Results show that distributed leadership significantly and positively predicts teachers’ job satisfaction, and teacher collaboration partially mediates the relationship between distributed leadership and teacher job satisfaction. The study not only provides a systematic explanation and empirical evidence for the promotion and enhancement mechanisms of distributed leadership on teachers’ job satisfaction from an international perspective, but also offers valuable insights for finding pathways to improve teachers’ job satisfaction and promote teacher development.